THE SUBTITLING OF â€œDEDAP DURHAKAâ€ LEGENDARY VIDEO - Murni Murni; Fanalisa Elfa; Rindilla Antika (INOVISH JOURNAL, 2023)
The aim of this research is making subtitling of Dedap Durhaka Legendary Video. The method used in this study was descriptive. In subtitling the video, the techniques of translation used in subtitling were word for word, literal and adaptation. The duration of the video was 24 minutes 53 second. There were several processes in making the English subtitle. They are collecting the materials, writing the script of video, translating the video and the last process was inserting the subtitle to video. The result of this study was about subtitling of Dedap Durhaka Lgendary Video. Based on the evaluation result, this subtitle can help to get students interest in learning English and make foreigners know the contents of video by reading the English subtitle.